Academic Administration of School Administrators in the Ariyamongkol School Network under the Rayong Primary Educational Service Area 2 Office - วีระพันธ์ สุชาดา; แก้วมงคล ทรงยศ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
The objectives of this research were: 1) to study the academic administration of school administrators in the Ariyamongkol Network under the Rayong Primary Educational Service Area Office 2; 2) to compare academic administration as classified by personal status; and 3) to investigate guidelines for academic administration within the Ariyamongkol Network under the Rayong Primary Educational Service Area Office 2. The research sample consisted of 155 school administrators and teachers in the Ariyamongkol Network, obtained through simple random sampling. The research instruments included a 5-point Likert scale questionnaire with an Index of Item-Objective Congruence (IOC) between 0.60-1.00 and a reliability coefficient of .980, as well as structured interviews with 5 school administrators. Data were analyzed using Mean, Standard Deviation, t-test, One-Way ANOVA, and content analysis. The research findings revealed that: • The overall academic administration of schools in the Ariyamongkol Network was at the highest level. • The comparison of academic administration classified by personal status showed that position and educational level yielded no significant differences. However, work experience resulted in a statistically significant difference at the .05 level. 3. The academic administration of the Ariyamongkol Network integrates robust systems with human understanding, beginning with supporting teachers in creating innovation, enhancing academic achievement, and developing students into sustainable, quality citizens.